2017
DOI: 10.1155/2017/6571089
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Polyphenolic Content of Beninese Honeys

Abstract: The physicochemical and phytochemical analyses of honeys (n = 50) from Sudanese, Sudano-Guinean, and Guinean areas of Benin were investigated. Results showed that dark amber is the dominant color. Moisture content ranged from 15.50% to 23.50%, and 72% of honeys respected the Codex Alimentarius recommendation. pH varied between 2.87 and 6.15, and free acidity ranged from 9.00 to 39.00 meq/kg. Electrical conductivity varied from 0.37 to 1.43 mS/cm. The content in fructose varied from 21.67% to 94.21%, and prolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…The average pH values of fresh and branded honey ranged from 4.35 to 7.05 and 4.6 to 5.35. Azonwade et al, 2018, Lokossou et al, 2017 reported pH of 5.08 and 5.00–5.48 respectively, showing almost the same range as found in the present research. However, Laredj and Waffa, 2017, Mohammed et al, 2017 recorded acidic pH values (4.17 and 4.20) in Algerian and Saudi honeys lower than present pH.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The average pH values of fresh and branded honey ranged from 4.35 to 7.05 and 4.6 to 5.35. Azonwade et al, 2018, Lokossou et al, 2017 reported pH of 5.08 and 5.00–5.48 respectively, showing almost the same range as found in the present research. However, Laredj and Waffa, 2017, Mohammed et al, 2017 recorded acidic pH values (4.17 and 4.20) in Algerian and Saudi honeys lower than present pH.…”
Section: Resultssupporting
confidence: 89%
“…However, Laredj and Waffa, 2017, Mohammed et al, 2017 recorded acidic pH values (4.17 and 4.20) in Algerian and Saudi honeys lower than present pH. In the same way EC ranges obtained by Bousaid et al (2018) (0.39–0.89 mS/cm), Lokossou et al (2017) (0.37–1.43 mS/cm) and Guler et al (2017) (0.250–0.90 mS/cm) in Tunasian honey, Beninese and Turkish honeys were more or less same as found in fresh (0.11–0.61 mS/cm) and branded (0.17–0.23 mS/cm) honey samples. The resulted variation in EC depends on the different floral origins of honeys.…”
Section: Resultssupporting
confidence: 71%
“…The samples varied in pH from 4.11 to 4.67, showing almost the same range as recorded by Laredj et al [39] and Elimam et al [66]. In the same way, electrical conductivity ranges obtained by Boussaid et al [67] (0.39-0.89 mS/cm), Lokossou et al [68] (0.37-1.43 mS/cm), and Guler et al [69] (0.250-0.90 mS/cm) in Tunisian, Beninese, and Turkish honey had more or less identical results to those found in our thyme honey samples (0.73-0.87 mS/cm).…”
Section: Physicochemical Properties Of Thyme Honeysupporting
confidence: 80%
“…A lower range has been reported for honey from Slovenia (44.8–241.4 mg/kg) [ 4 ], Romania (120.0–260.5 mg/kg) [ 25 ], Italy (108.2–146.7 mg/kg) [ 26 ] and Portugal (198.5–214.3 mg/kg) [ 27 ]. Higher content was found in honey from Spain (339–1542 mg/kg) [ 28 ], Brazil (611.1–1753.9 mg/kg) [ 29 ], Italy (165–1333 mg/kg) [ 30 ], Sudan (559.7 and 2249.9 mg/kg) [ 31 ] and Turkey (343.7 and 4707 mg/kg) [ 32 ]. In Spanish honeys, as many as 49 phenolic compounds were detected, of which 46 were quantified [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…The world literature also reports varied total flavonoid content in honey from different countries. In honey from Sudan, the concentrations of these compounds ranged from 14.3 to 298.1 mg GAE/kg [ 31 ], and in Romanian honey from 10.8 to 32 mg QE/kg [ 25 ]. These ranges are comparable to those obtained in the present study.…”
Section: Resultsmentioning
confidence: 99%